ADAPTIVE MARKET? A NEW HYPOTHESIS? - Bayu Laksma Pradana (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2018)
The efficient market hypothesis (EMH) has been challenged by behaviourists for decades. Is market predictable? and how rational human beings prone to make flaws in making decisions are two general questions that still debatable until nowadays. A long argument between Rationalists and Behaviorists. A new theory emerged to find a way out and became the “middle way”. It gave justifications that those previous theories have both their own strengths and also weakneses. Combining biology, neuro science, and evolution, The MIT Professor seemed to believe that finance and market today are more like evolutionary biology than physic. From time to time market adapts with environment, change in circumstances lead to change in behavior and methodology; this is what Andrew Lo called Adaptive Market. This literature study briefly explains the very start evidence about Efficient Market Hypothesis and how behaviour finance becomes the opponent of EMH. How adaptive market expands the horizon of interdiciplinary studies also will be presented in thorough manner. In conclusion, the new theory gives many proves that market is adaptive. However in contrast with behavior finance, adaptive market has more comprehensive reasons explaining the financial and economic environment that has been changed recently.